The Effect of Staff Competence, Customer Satisfaction, and Service Quality on Cargo Shipping Service User Loyalty - Lermatan, Esterlinus Edwin; Jaya Sakti, Reza Fauzi; Ghafar, Abdul; Widiawati, Sarovah; Krisnawati, Siti; Prakoso, Otto Sugiharto (Siber Journal of Transportation and Logistics, 2023)
Abstract: The Effect of Staff Competence, Customer Satisfaction and Service Quality on Cargo Shipping Service Users is a scientific article of literature study within the scope of the combination of human resources and marketing management. The purpose of this article is to build hypotheses of influence between variables that will be used in further research. The object of research is on online libraries, Google Scholar, Mendeley, and other academic online media. Research methods with library research sourced from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) Staff Competence affects Cargo Shipping Service Users; 2) Customer Satisfaction affects Cargo Shipping Service Users; and 3) Service Quality affects Cargo Shipping Service Users.